Implementing the Ages and Stages Questionnaires in a Montessori Setting - Postlewaite, Elyse; Avello, Dalia; Massie, Catherine; Sabater, Ayize (Journal of Montessori Research, 2024)
Montessori educators face increasing demands to support growing numbers of students who have developmental delays or disabilities, and early detection and support are essential. Yet, detecting developmental delays is a complex task, and early childhood educators do not typically receive specialized training. The Ages and Stages Questionnaires (ASQ) is a set of valid and reliable developmental screening tools widely used in education and health settings, but ASQ use has not been assessed in Montessori settings. In a pre/post, multimethod design, this study examined the perceptions and impact of an ASQ training—adapted for Montessori settings—for guides and administrators. The results suggest the ASQ training and implementation of its tools were perceived as beneficial and valuable. The training positively influenced participants’ attitudes and beliefs, skills and knowledge, confidence and self-efficacy, and access to resources. Alumni of the training had similar attitudes and beliefs, as well as confidence and self-efficacy, compared to recent trainees, although alumni’s skills and knowledge, as well as access to resources, were more advanced than the recent trainees. Qualitative findings also point to the benefits of the training while highlighting the realities, needs, and challenges Montessori educators face. This study provides evidence that Montessori educators benefit from ASQ developmental screening training. Through ASQ training and implementation, Montessori educators can gain a better understanding of students’ developmental milestones, more effectively observe their students’ behaviors, and more confidently advocate for students’ support needs.